Force Production and Electromyographic Activity during Different Flywheel Deadlift Exercises - Sergio Maroto-Izquierdo; David García-López; Marco Beato; Iker J. Bautista; José L. Hernández-Davó; Javier Raya-González; Fernando Martín-Rivera (MDPI AG, 2024)
This study aimed to characterize and compare force production and muscle activity during four flywheel deadlift exercises (bilateral [Bi] vs. unilateral [Uni]) with different loading conditions (vertical [Ver] vs. horizontal [Hor]). Twenty-three team-sport athletes underwent assessments for exercise kinetics (hand-grip force), along with surface electromyography (sEMG) of the proximal (BFProx) and medial biceps femoris (BFMed), semitendinosus (ST), and gluteus medius (GM). Mean and peak force were highest (p < 0.001) in Bi + Ver compared with Bi + Hor, Uni + Ver, and Uni + Hor. Although no significant differences were observed between Bi + Hor and Uni + Ver, both variants showed higher (p < 0.001) average force and peak eccentric force when compared with Uni + Hor. The presence of eccentric overload was only observed in the vertically loaded variants. Bi + Ver and Uni + Ver showed higher (p < 0.05) sEMG levels in BFProx and BFMed compared with the Uni + Hor variant. In addition, Uni + Ver registered the largest GM and ST sEMG values. In conclusion, the vertical variants of the flywheel deadlift exercise led to higher muscle force production and sEMG compared with their horizontal counterparts. Both Bi + Ver and Uni + Ver may be effective in promoting an increase in hamstring muscles activity and muscle force at long muscle length, while the Uni + Ver variant may be more effective in promoting GM and ST involvement.